Trajetória político-intelectual e representações da Revolução Mexicana nas obras de Martín Luis Guzmán (1915-1969) - Carolline Martins de Andrade (2018)
In this dissertation we sought to understand and analyze the meanings of the Mexican Revolution in some works of the writer Martín Luis Guzmán, and the way in which these conceptions found themselves associated with his political and intellectual trajectory. In this attempt, our timeframe extended from the first years of the twentieth century, which corresponds to the configuration of the Mexican intellectual environment, until 1969, when Guzmán positioned himself favorably toward the repression of students in October 1968, marking the path that would lead him to a temporary but significant period of being forgotten by Mexican academic research. The sources that served as the basis for the constitution of this text are varied and include essays, newspaper articles, novels, memorialistic texts, letters, political and intellectual speeches, and programs of party creation. For the development of this study, we utilized elements that are part of the theoretical framework of both intellectual history and the history of intellectuals, as well as reflections on history, literature, and memory. In short, we analyzed the political and intellectual trajectory of Martín Luis Guzmán, his participation as one of the consecrated authors within what is understood as the Romance of the Revolution, and his insertion into the debate of the ramifications of the Revolution and of the construction of the post-revolutionary state, while always aiming to note his political action in Mexican power plays during this long displacement throughout the twentieth century.